INTEGRATING ISLAMIC RELIGIOUS EDUCATION AND SCIENCE IN HOLISTIC ISLAMIC EDUCATION : STRENGTHENING STUDENTS’ RELIGIOUS COMMITMENT - Sugiyanto; Imron Arifin (Program Studi Magister Pendidikan Agama Islam Universitas Hasyim Asy’ari Tebuireng Jombang m Asy'ari, 2021)
This study aims to analyze the integration of Islamic Religious Education (PAI) and Natural Sciences (IPA) within the framework of holistic Islamic education and its implications for strengthening students’ religious commitment at the senior high school level. The research employed a qualitative descriptive approach conducted at SMA Primaganda Jombang. Data were collected through in-depth interviews, classroom observations, and document analysis, and analyzed using data reduction, data display, and verification with triangulation techniques. The findings reveal that knowledge integration is implemented through institution-based religious vision, pedagogical designs linking scientific concepts with tawhidic values, and reflective learning practices that position science as a medium for internalizing spiritual awareness. This integration contributes to strengthening students’ belief, religious practice, religious knowledge, and moral consequences. The study concludes that integrating PAI and IPA within a holistic Islamic education framework not only overcomes the dichotomy of knowledge but also fosters rational and sustainable religious consciousness.